2007
DOI: 10.1002/jmri.20854
|View full text |Cite
|
Sign up to set email alerts
|

Low‐field musculoskeletal MRI

Abstract: Since it was first introduced in the field of medical imaging in the early 1980s, MRI has become essential for the diagnosis and treatment of musculoskeletal conditions. Most imaging in the United States is performed on high-field (Ͼ1.0T), whole-body scanners. However, for reasons discussed below, imaging at low (Ͻ0.5T) and medium (0.5-1.0T) field strengths using small, low-cost, easily installed scanners in imaging centers and physicians' offices is gaining increasing popularity. Such scanners can be very use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 30 publications
(31 reference statements)
2
69
0
Order By: Relevance
“…Several review articles on low-field versus high-field MRI of the extremities agree that low-field strength MRI systems provide the ability to diagnose substantial pathologies within the ligaments and menisci of the knee [3,9,19]. This is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Several review articles on low-field versus high-field MRI of the extremities agree that low-field strength MRI systems provide the ability to diagnose substantial pathologies within the ligaments and menisci of the knee [3,9,19]. This is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 95%
“…But this was not associated with the used MRI field strength. A reason for the latter result may be that radiologists are undersensitised for recognising lateral meniscal lesions because they are less common than medial meniscal or ACL tears [19]. However, it should be stressed that specialised training is required for quality control and image interpretation in lowfield MRI.…”
Section: Discussionmentioning
confidence: 98%
“…On the other side there are two limitations that need to be acknowledged in the present study. Although the clinically accepted range of MRI covers from 0.2T to 3T (Ghazinoor et al 2007), the use of low-field MRI in this study made the detection of small cartilage abnormalities very challenging. The second point concerns to the sample size and the proximity of the two time endpoints for the euthanasia, which gave similar results, making possible to combine data for each treatment from both the 12-and 20-week groups for the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The caveat is the expertise of the user and image reader. While there is no question that the higher field MRI units (greater than 1.0 T) provide better quality images, Ghazinoor et al 11 have concluded that low-field scanners have demonstrated high diagnostic value in musculoskeletal pathology, although image interpretation is impacted by the training and experience of the reader and they may not be optimal for diagnosis of some structures, such as the meniscus of the knee.…”
Section: Field Strengthmentioning
confidence: 99%